2006
DOI: 10.1158/0008-5472.can-05-2292
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of Prolactin as an Invasion Suppressor Hormone in Breast Cancer Cells

Abstract: Prolactin hormone (PRL) is well characterized as a terminal differentiation factor for mammary epithelial cells and as an autocrine growth/survival factor in breast cancer cells. However, this function of PRL may not fully signify its role in breast tumorigenesis. Cancer is a complex multistep progressive disease resulting not only from defects in cell growth but also in cell differentiation. Indeed, dedifferentiation of tumor cells is now recognized as a crucial event in invasion and metastasis. PRL plays a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 60 publications
2
86
2
1
Order By: Relevance
“…While PRL signals via the Jak2/Stat5 pathway during mammary development are well recognized, relatively little is known about the role of other PRL-initiated signals, and their interrelationships in physiologic and pathologic processes. Recently, PRLactivated Stat5 has been reported to reduce processes associated with tumor aggression in vitro (Sultan et al, 2005;Nouhi et al, 2006), consistent with better prognoses in vivo (Cotarla et al, 2004;Nevalainen et al, 2004), prompting the suggestion that PRL signals may promote a more differentiated tumor phenotype. The present study extends our previous reports of PRL activation of another pathway, driving expression of AP-1 target genes associated with tumor progression.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While PRL signals via the Jak2/Stat5 pathway during mammary development are well recognized, relatively little is known about the role of other PRL-initiated signals, and their interrelationships in physiologic and pathologic processes. Recently, PRLactivated Stat5 has been reported to reduce processes associated with tumor aggression in vitro (Sultan et al, 2005;Nouhi et al, 2006), consistent with better prognoses in vivo (Cotarla et al, 2004;Nevalainen et al, 2004), prompting the suggestion that PRL signals may promote a more differentiated tumor phenotype. The present study extends our previous reports of PRL activation of another pathway, driving expression of AP-1 target genes associated with tumor progression.…”
Section: Discussionmentioning
confidence: 86%
“…High levels of activated Stat5 also are found in a substantial proportion of human breast tumors, which interestingly correlate with a better prognosis (Cotarla et al, 2004;Nevalainen et al, 2004). Recent investigations of breast cancer cell lines in vitro have shown that activated Stat5 inhibits invasion and the epithelial to mesenchymal transition (Sultan et al, 2005;Nouhi et al, 2006). Together, these studies suggest that Stat5 may play complex roles in mammary oncogenesis, augmenting tumor development, but opposing tumor progression.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, the summarized data provide a generalized view of the implication of the central cytokine signaling in tumor development of [33] and inhibitory role in metastasis progression [45] ). Moreover, it can help us to decipher new mechanisms of activation of the components of the JAK-STAT pathway like receptor and/ or ligand nuclear localization.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in some models JAK1 and 2 also play an antitumorigenic role [43] . Prl induced activation of JAK2 prevents breast cancer cells mesenchymal transition and acts as an invasion suppressor [44,45] . Reduced phosphorylation of STAT5 in breast cancer highlights patients with a worse prognosis of disease development [46] .…”
Section: Jak-stat Signaling and Carcinogenesismentioning
confidence: 99%
“…(4) Indeed, EMT from mammary organoid cultures is used by other researchers as a proxy for malignant invasion (as in mammary carcinoma) rather than normal development. (8)(9)(10) It is possible, therefore, that Nelson et al…”
Section: Tgfb As a Controller Of Patterningmentioning
confidence: 99%